A-Track: An Ontological Approach to Assisting Anxiety Management - Schroeder, Gustavo Lazarotto; Paula, Leonardo dos Santos; Francisco, Rosemary; Barbosa, Jorge Luis Victória (Anais do Simpósio Brasileiro de Computação Aplicada à Saúde (SBCAS); 2025: Anais do XXV Simpósio Brasileiro de Computação Aplicada à SaúdeDO - 10.5753/sbcas.2025.6928, 2025)
Anxiety, a natural survival mechanism, becomes chronic under modern stressors, escalating into chronic disorders with multifaceted health impacts. While early detection is crucial, healthcare systems struggle with scalability. This study introduces the A-Track Ontology, a digital tool designed to model anxiety through personalized context histories. Validated through logical consistency, domain coverage, and utility assessments, the ontology synthesizes multimodal data into actionable insights for proactive intervention. Integrating ontological reasoning with real-world context awareness, this approach addresses clinical scalability gaps, enabling personalized, data-driven strategies for anxiety management.